2020
DOI: 10.1002/aenm.202000368
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Electrolytes for Fast‐Charging High‐Voltage Lithium‐Ion Batteries in Wide‐Temperature Range

Abstract: IntroductionLithium (Li)-ion batteries (LIBs) have now been the indispensable power sources for portable electronic devices, electric vehicles, stationary or grid applications, etc. [1] However, further efforts on extending the cycle life, rate capability, energy density and working temperature range and improving the safety of LIBs are still facing significant challenges for their large-scale applications. Focusing on the increase in energy density of a battery, the possible approach is to use the high capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
180
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(185 citation statements)
references
References 37 publications
4
180
1
Order By: Relevance
“…29,30 Considering the high cost and viscosity of SCE, diluting SCE with non-polar solvents emerged in recent years as an alternative to mitigate these issues. [31][32][33] The diluted SCE is termed localized superconcentrated electrolytes (LSCE) because the local solvation structure of LSCE is very similar to that of SCE, and therefore they belong to the same methodology.…”
mentioning
confidence: 99%
“…29,30 Considering the high cost and viscosity of SCE, diluting SCE with non-polar solvents emerged in recent years as an alternative to mitigate these issues. [31][32][33] The diluted SCE is termed localized superconcentrated electrolytes (LSCE) because the local solvation structure of LSCE is very similar to that of SCE, and therefore they belong to the same methodology.…”
mentioning
confidence: 99%
“…For example, Zhang et al showed that at low temperatures (‐20 and −30 °C), Gr/NCA cells deliver higher capacity with a LiBF 4 electrolyte than with a LiPF 6 counterpart while the LiBF 4 electrolyte has lower ionic conductivity. Similarly, Yamada et al demonstrated that a Li/Gr cell with 3.6 M LiFSI‐DME electrolyte having a lower ionic conductivity (7.2 mS cm −1 ) outperforms that with 1.0 M LiPF 6 ‐EC‐DMC electrolyte (∼10 mS cm −1 ); Zhang et al reported that at 5 C, a Gr/NMC811 cell with 2.8 mAh cm −2 of NMC811 loading demonstrates higher capacity with a 1.4 m LiFSI DMC‐EC‐TTE electrolyte (2:0.2 : 3 by mol, 1.07 mS cm −1 ) than with a 1.0 m LiPF 6 EC‐EMC electrolyte (3 : 7 by wt+2 wt% VC, 6.07 mS cm −1 ). The above results reveal that the ionic conductivity of the electrolytes is not the only factor governing the fast‐charging capability.…”
Section: Challenges and Strategiesmentioning
confidence: 96%
“…For the mixture of solvents, cyclic ethylene carbonate (EC) is considered to be an indispensable co-solvent for the formation of robust solid-electrolyte-interphase (SEI) on the graphite anode, and the other solvent can be a linear dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylmethyl carbonate (EMC), or their mixture for reduced viscosity and low freezing temperature of the electrolytes. In some cases, small amounts of esters [7][8][9] or ethers 10,11 that have a low boiling point and acceptably chemical stability are added to enable operations at low temperatures or/and high current rates. However, such benefits often come with a trade-off in reversibility and lifetime.…”
Section: Current Statusmentioning
confidence: 99%
“…Therefore, the solutions to the first question should be centered on the second and third steps as shown in Figure 1. While fast charge necessitates high ionic conductivity, several studies revealed that some electrolytes with LiBF 4 26,27 and LiFSI 11,28 have lower conductivity, however, the resultant batteries exhibit higher capacity and lower polarization at low temperatures and high rates compared with those using the conventional LiPF 6 ‐carbonate electrolytes. Although the mechanism for the above phenomena is yet unclear, these findings point out a fact that the ionic conductivity of the electrolytes is not the only factor governing the fast‐charging capability.…”
Section: Future Needs and Prospectsmentioning
confidence: 99%